TRANSPORTASI ANTARMODA KOMUTER PNS DI PROVINSI MALUKU UTARA - Raudha Hakim (Journal of Science and Engineering, 2018)
The transfer of the provincial capital from Ternate to Sofifi caused almost allgovernment activities to be transferred to Sofifi. This is indicated by the increasingnumber of commuters who travel between islands with surrounding islands or districts(hinterland) or between regions within the city. Sea transportation as a means ofconnecting between islands is still very minimal, lack of infrastructure, limited numberof transportation to high transportation costs. The purpose of this study was to determinethe characteristics of PNS commuters in the island cluster area and analyze the chain ofcommuter PNS trips in the island cluster region in North Maluku province. Theinterview survey was conducted to determine various personal characteristics andpatterns of commuter travel chains. The results of this study are expected to provide anoverview of the characteristics of the computer travel chain in the island cluster regionin North Maluku Province.